INTERNALIZATION OF MULTICULTURAL VALUES IN ARABIC LEARNING - Ubadah, Ubadah (State Institute of Islamic Studies (IAIN) Palu, 2021)
Internalization of multicultural values ​​has become the concern of many researchers today, but how the process of internalization in learning, especially language learning, is still a little done. For this reason, this study focuses on the approach of internalizing multicultural values ​​in learning Arabic at one of the State Madrasah Aliyah schools in the city of Palu. This research uses a qualitative case study approach. The data were collected by means of observation, in-depth interviews, and from written documents. The results showed that multicultural values ​​were internalized through the curriculum, syllabus, and lesson plans (RPP). The process of integrating multicultural values ​​which includes spiritual values ​​and social attitudes is carried out through semi-contributive, semi-additive, and indirect teaching processes. The integrated values ​​include spiritual attitudes and social attitudes that encourage the growth of multiculturalism values.